Examining the Relationship Between Motor Skills and Academic Achievement in School-Aged Children and Adolescents: A Systematic Review with Implications for Sports Psychology - Lijing Wang; Kexin Chen; Lijuan Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Purpose: This systematic review explores the relationship between motor skills and academic achievement in primary and secondary school students, with a specific focus on gross and fine motor skills and their impact on performance across different academic subjects. The study provides insights relevant to sports psychology and educational strategies for enhancing cognitive and physical development. Method: Five electronic databases, including Web of Science, PubMed, PsycINFO, SPORT Discus, and Academic Search Premier, were searched in October 2022. Semi-quantitative assessment methods were used to analyze the results of the 78 studies included in this review. Results: The findings indicate that both gross (positive correlation in 65.0–62.5% of studies) and fine motor skills (positive correlation in 83.3–80% of studies) are positively associated with overall academic performance and language achievement. Fine motor skills showed strong positive correlations with math (75.6%), reading (71.1%), writing (66.7%), and spelling (60.0%) scores. In contrast, the relationship between gross motor skills and achievement in math (51.4%), reading (53.8%), and spelling (50.0%) was less certain. Conclusion: These findings emphasize the importance of fostering motor skill development, particularly in primary school students. Tailored motor skill interventions should be designed to target specific academic outcomes based on the unique benefits of gross and fine motor skills. From a sports psychology perspective, the integration of motor skill development into physical education and sports activities can support cognitive and academic growth, highlighting the critical role of physical activity in holistic education.